Muticultural Approach in Composing for Malay Gamelan in 21st Century (Proceeding of the International Conference on Arts and Humanities, 2021)
This study was carried out to compose new music for Malay gamelan using combinations of traditional Malay gamelan elements and Malay folk tunes with Western composition techniques (multicultural approach). Three original compositions, Khabar Angin Tenggara (2014), Adiwira dalam Bb (2015) and Jong (2017) highlighting Malay gamelan has been composed for this purpose. They feature the Malay gamelan as an ensemble itself, sape, and four voices orchestrated with Malay gamelan ensemble, and a bonang played with four hands. Elements of aleatoric, unconventional instrumentation in the context of the traditional Malay gamelan setup and Malay folk tunes have been incorporated into these new works. This paper will illustrate the creative process and related issues of these compositions with the aims of attaining the multicultural elements that can be incorporated into future works. These multicultural composition techniques will perhaps encourage the development of captivating aesthetic appeal for a new composition for Malay gamelan and promote the elements of local Malay folk tunes to a wider audience.
Keywords: multicultural; music composition; malay gamelan; 21st century